The control and importance of hyaluronan synthase expression in palatogenesis - Galloway, Jennifer; Jones, Sarah; Mossey, Peter; Ellis, Ian (Frontiers in Physiology, 2013)
Development of the lip and palate involves a complex series of events that requires the close co-ordination of cell migration, growth, differentiation and apoptosis. Palatal shelf elevation is considered to be driven by regional accumulation and hydration of glycosoaminoglycans, principally hyaluronan (HA), which provides an intrinsic shelf force, directed by components of the extracellular matrix (ECM). During embryogenesis, the extracellular and pericellular matrix surrounding migrating and proliferating cells is rich in HA. This would suggest that HA may be important in both shelf growth and fusion. TGFβ3 plays an important role in palatogenesis and the corresponding homozygous null (TGFβ3 -/-) mouse, exhibits a defect in the fusion of the palatal shelves resulting in clefting of the secondary palate. TGFβ3 is expressed at the future medial edge epithelium (MEE) and at the actual edge epithelium during E14.5, suggesting a role for TGFβ3 in fusion. This is substantiated by experiments showing that addition of exogenous TGFβ3 can ‘rescue’ the cleft palate phenotype in the null mouse. In addition, TGFβ1 and TGFβ2 can rescue the null mouse palate (in vitro) to near normal fusion. In vivo a TGFβ1 knock-in mouse, where the coding region of the TGFβ3 gene was replaced with the full-length TGFβ1 cDNA, displayed complete fusion at the mid portion of the secondary palate, whereas the anterior and posterior regions failed to fuse appropriately. We present experimental data indicating that the three Has enzymes are differentially expressed during palatogenesis. Using immunohistochemistry and embryo sections from the TGFβ3 null mouse at days E13.5 and E14.5, it was established that there was a decrease in expression of Has2 in the mesenchyme and an increase in expression of Has3 in comparison to the wild type mouse. In vitro data indicate that HA synthesis is affected by addition of exogenous TGFβ3. Preliminary data suggests that this increase in HA synthesis, in respons